The costs of natural gas dependency: Price shocks, inequality, and public policy - Mats Kröger; Maximilian Longmuir; Karsten Neuhoff; Franziska Schütze (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Natural gas prices in Germany saw a strong increase at the end of 2021, subsequently worsening with the start of the war in Ukraine in February 2022, raising concerns about the distributional consequences. Our study shows that low-income households are affected the most by the natural gas price increase. Low-income households pay at the median 11.70 percent of their equivalent income on gas bills, compared to 6.21 percent in 2020. Contrarily, high-income households pay at the median 2.41 percent, compared to 1.52 in 2020. Natural gas expenditures are higher for tenants in detached houses and in houses with no double glassing or thermal insulation. Our policy analysis builds on an exploration of new energy expenditure data in 2020 provided by the German Socio-Economic Panel, and shows that a well-targeted subsidy scheme can be more effective for reducing inequality and less costly than a subsidy for all households. Additionally, the introduction of a minimum energy-efficiency standard for buildings can help reduce inequality in the medium-term.
Keywords: D30; Q41; I38; 330; Natural gas prices; income distribution; energy efficiency; building retrofit